Dietary pattern and risk of multiple sclerosis - Jahromi, Soodeh Razeghi (Tehran University of Medical Sciences, 2012)
BACKGROUND: It has been suggested that nutrition might play a role in the etiology of multiple sclerosis (MS). However, dietary patterns associated with MS risk are unknown. This study was conducted to compare the dietary patterns of patients with MS and healthy controls to find the relationship between dietary patterns and MS. METHODS: Usual dietary intake of 75 women with relapsing/remitting MS (RRMS) and 75 healthy controls were assessed with a food frequency questionnaire consisting of 168 food items. To define major dietary patterns, we used factor analysis. Multivariate logistic regression was used to assess the relationship between dietary patterns and risk of MS. RESULTS: Traditional pattern (high in low-fat dairy products, red meat, vegetable oil, onion, whole grain, soy, refined grains, organ meats, coffee, and legumes) was inversely related to the risk of MS [odds ratio (OR) = 0.15; 95% confidence interval (CI): 0.03-0.18; P = 0.028]. A similar inverse relationship was noted between MS risk and lacto-vegetarian (high in nuts, fruits, French fries, coffee, sweets and desserts, vegetables, and high-fat dairy products) and vegetarian (high in green leafy vegetables, hydrogenated fats, tomato, yellow vegetables, fruit juices, onion, and other vegetables) patterns (OR = 0.31; 95% CI: 0.12-0.82; P = 0.018 and OR = 0.42; 95% CI: 0.19-0.90; P = 0.026, respectively). In contrast, the prevalence of MS was higher in those who had high animal fat dietary pattern (high in animal fats, potato, meat products, sugars, and hydrogenated fats and low in whole grains) (OR = 1.99; 95% CI: 1.63-2.94; P < 0.005). CONCLUSION: Our findings showed that the risk of RRMS can be affected by major dietary patterns.